LIFE PREDICTION OF METRO OBSTACLE DETECTOR BASED ON FATIGUE TEST AND FRACTURE SIMULATION - LI XiangJie; YANG GuangWu; XIAO ShouNe; ZHU Tao; YANG Bing (Jixie qiangdu)
Using the vibration excitation spectrum of IEC61373, the subway bogie obstacle detector was taken as the research object. The random vibration fatigue strength of the obstacle detector was studied by combining the finite element method and bench vibration test, and the remaining life at the fatigue weak points of the aluminum beam welded joints was predicted. Based on the frequency domain method, combined with Miner’s linear accumulation damaging theory, the simulation life results of the obstacle detector under acceleration excitation were obtained, then compared with the bench vibration testing results to verify the accuracy of the fatigue simulation analysis. Moreover, the sub-model boundary technique was used to separate the aluminum beam, and the stress spectrum of the fatigue weak points was equivalently converted. At last, the remaining life was predicted after inserting the initial cracks at the evaluation points. The result indicated also that it is reasonable to evaluate the remaining life of aluminum alloy welded joints with initial cracks based on fracture mechanics, which provides the certain reference for engineering applications.